1991
DOI: 10.1038/jcbfm.1991.61
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Postischemic Neuronal Necrosis in Gerbils

Abstract: Twenty-four hour postischemic neuronal necrosis was compared in male vs. female Mongolian gerbils subjected to a 3-h period of severe incomplete hemispheric ischemia produced by unilateral carotid occlusion. The incidence of stroke-prone males was 42.9% versus 26.7% for the females. Among the stroke-prone animals, the males displayed significantly greater neuronal necrosis at 24 h after ischemia compared to the females in the cerebral cortex and CA1 region of the hippocampus. In the CA1 region of the stroke-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
2
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(141 citation statements)
references
References 17 publications
5
130
2
3
Order By: Relevance
“…The increased sensitivity of males to the deleterious effects of anesthesia is consistent with numerous reports in both humans and animals (Hall et al, 1991;Hurn et al, 2005;Rogers and Wagner, 2006;Yager et al, 2005). Across both sexes, isoflurane had the most pronounced negative repercussions, resulting in a 20-26% reduction in hippocampal volume and neuron number.…”
Section: Males More Sensitive Than Females To Neonatal Anesthesiasupporting
confidence: 75%
“…The increased sensitivity of males to the deleterious effects of anesthesia is consistent with numerous reports in both humans and animals (Hall et al, 1991;Hurn et al, 2005;Rogers and Wagner, 2006;Yager et al, 2005). Across both sexes, isoflurane had the most pronounced negative repercussions, resulting in a 20-26% reduction in hippocampal volume and neuron number.…”
Section: Males More Sensitive Than Females To Neonatal Anesthesiasupporting
confidence: 75%
“…12,20 Another possible mechanism of neuroprotection by estrogen might be by virtue of its strong antioxidant properties, resulting in more oxidative damage in males. 2 Improved recovery after SCI in females may also be due to effects of estrogen on anti-apoptotic proteins such as bcl-2. Apoptosis after SCI has been confirmed by many groups including ours.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Hall et al 2 showed that 24 h after incomplete ischemia produced by temporary unilateral carotid occlusion, male gerbils demonstrated significantly more neuronal loss in the cerebral cortex and the CA1 of the hippocampus than did females. Alkayed et al 5 reported that using a model of temporary middle cerebral artery (MCA) occlusion both Wistar and hypertensive female rats had smaller infarcts in the cortex and caudateputamen than did males of the same strain.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in brain structures and mechanisms occur in other brain regions besides hypothalamus, such as hippocampus, and they appear to be involved in aspects of cognitive function and other processes that go beyond the reproductive process itself, such as the higher incidence of depression in women and of substance abuse in men (122). There are also sex differences in the severity of brain damage resulting from transient ischemia (49) and sex differences in the response of the brain to lesions (104) and to severe, chronic stress (100,141). A recent study has shown that the stress-induced atrophy of apical dendrites of CA3 pyramidal neurons occurs in male rats but not in female rats (42).…”
Section: Importance Of Sex Differences and Sex Hormonesmentioning
confidence: 99%